The Effect of Financial Literacy and Risk Tolerance on Investment Decisions - Ni Made Mega Abdi Utami; Putu Rany Wedasuari (Universitas Islam Lamongan, 2023)
This study aims to determine the effect of financial literacy and risk tolerance on investment decisions. This research was conducted on 64 students who joined the capital market study group at the Bali State Polytechnic. The sampling method used is saturated sampling. Based on the results of the multiple regression analysis that has been carried out, it was found that financial literacy has an effect on investment decisions and risk tolerance has an effect on investment decisions.